PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MATERI GAGASAN POKOK PARAGRAF DI SD ISLAM PB SOEDIRMAN JAKARTA - Syamzah Ayuningrum (ITB AAS INDONESIA Surakarta, 2022)
The purpose of this study is to improve the learning outcomes of Indonesian language with the main idea of paragraphs through the application of the CIRC learning model. The research method used is classroom action research using a qualitative approach. This research includes 2 cycles where each cycle includes 4 stages, namely planning, action, observation and reflection. This research was carried out at SD Islam PB Sudirman with 32 students as research subjects, while data were collected through tests, interviews, observation and documentation. 56 Cycle I = 74.68, and Cycle II = 82.34. This study concludes that using the CIRC learning model can improve learning outcomes for the main idea paragraph material